COGNITIVE IMPAIRMENT IN BIPOLAR DISORDER - Latalova, Klara; Prasko, Jan; Diveky, Tomas; Velartova, Hana (Biomedical papers, 2011)
Aim: Provide an overview of how bipolar disorder affects cognitive function in patients.Methods: MEDLINE and PsycInfo data bases were searched for articles indexed by the combinations of MESH term or key word "bipolar disorder" with the following terms: "cognition", "memory", "neuropsychology", "neuropsychological tests", "lithium", "anticonvulsants", "antipsychotics", and "schizophrenia". Constraints limiting time period of publications or their language were not applied. Reference lists of publications identified by these procedures were hand-searched for additional relevant citations.Results: There is evidence of stable and lasting cognitive impairment in all phases of bipolar disorder, including the remission phase, particularly in the following domains: sustained attention, memory and executive functions. But research on the cognitive functions has yielded inconsistent results over recent years. There is a growing need for clarification regarding the magnitude, clinical relevance and confounding variables of cognitive impairment in bipolar patients. The impact of bipolar illness on cognition can be influenced by age of onset, pharmacological treatments, individual response, familial risk factors, and clinical features. In addition to the mood state, cognitive performance in bipolar patients is influenced by seasonality.Conclusion: Previous optimistic assumptions about the prognosis of bipolar disorder were based on the success of the control of mood symptoms by pharmacotherapy. However, it is now clear that the "remitted" euthymic bipolar patients have distinct impairments of executive function, verbal memory, psychomotor speed, and sustained attention. Mood stabilizers and atypical antipsychotics may reduce cognitive deficits in certain domains and may have a positive effect on quality of life and social functioning.
Keywords: Bipolar disorder/Cognitive impairment/Genetics/Mood stabilizers/Cognitive tests/Quality of life